2021
DOI: 10.47836/ifrj.28.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR assay for species identification of meat and dairy products from buffalo (Bubalus bubalis), cattle (Bos indicus and Bos taurus), goat (Capra hircus), and sheep (Ovis aries)

Abstract: Cases of fraudulent meat and dairy products have increased worldwide, especially in developing countries. To determine the misrepresented animal species, appropriate tools in routine monitoring should be available for food inspections. In the present work, a multiplex polymerase chain reaction assay for species identification of products from ruminants including buffalo, cattle, goat, and sheep was developed. The primer set KUMUT_cFarmSp1 was composed of five species-specific primers and a pair of positive-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Laboratory samples indicated that all samples were appropriately confirmed at 100%. Comparing our results to those in the literature showed that they were about the same or better in terms of specificity, sensitivity, and cost (Denyingyhot et al, 2022;Edwards & Gibbs, 1994;Galal-Khallaf, 2021;Lourenço et al, 2022;Roig et al, 2022;Sangthong et al, 2021;Yanaso et al, 2021;Zhao et al, 2021).…”
Section: Resultssupporting
confidence: 72%
“…Laboratory samples indicated that all samples were appropriately confirmed at 100%. Comparing our results to those in the literature showed that they were about the same or better in terms of specificity, sensitivity, and cost (Denyingyhot et al, 2022;Edwards & Gibbs, 1994;Galal-Khallaf, 2021;Lourenço et al, 2022;Roig et al, 2022;Sangthong et al, 2021;Yanaso et al, 2021;Zhao et al, 2021).…”
Section: Resultssupporting
confidence: 72%
“…In the study conducted by Sangthong et al . (2021), the detection of different species in various dairy products was investigated using multiplex PCR. In the study, the detection limit of the PCR method was 0.1 ng DNA, and no species other than the one declared on the label was detected in any dairy product analysed.…”
Section: Discussionmentioning
confidence: 99%